Education, social reform and philosophical development : evidence from the past, principles for the future - Pring, Richard (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Reflecting on the meaning and purpose of an education at the mercy of political changes and innovation, this book considers the social, historical, religious and cultural contexts that define education systems. With a particular focus on how historical contexts shape the nature of education and its relevance to wider society, it explores the history of education in relation to social reform, economic relevance and raising standards. The first part of the book describes the developing system of education within England and Wales from the 19th century, with reference to the growing consciousness of the need for 'education for all'. The second part identifies key philosophical influences on the evolving understandings of education, and thereby of the developing policies and arrangements made in the light of those understandings which they generated. Finally, the third part of the book revisits the 'aims of education' in the light of the historical development and the philosophical critiques. This book will be of great interest to academics, researchers, postgraduate students and policy makers interested in the history of education and the moments that have defined it"--
Introduction : historical understanding and philosophical reflection -- Developing pattern and meaning of education from early 19th century -- Apprenticeships and practical learning : lessons to be learnt -- Primary and secondary education for all -- Further education and youth service -- The shifting sands of qualifications -- Higher education : its changing nature -- Religious Influence : education and faith schools -- Changing political control -- Summary of changing concept of 'education' -- Utilitarianism, idealism, and socialism -- Positivism, post-modernism and wisdom of the market -- Pragmatism -- Respect for truth : problems of political discourse -- Aims of education : human flourishing and development of persons.
Keywords: Education -- Social aspects; Education -- Aims and objectives; Education -- Philosophy; Education -- Great Britain -- History; EDUCATION / History